Effect of Fortification of Sour Anchovy Flour (Stolephorus sp.) in the Manufacture of Stick towards Consumer Acceptance - Ambarita, Befrison Utama; Sumarto, Sumarto; Sari, N. Ira (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Thisresearchwas intended to determine the effect of fortificatonof sour anchovy (Stolephorus sp.)flour in the manufacture of the stick towards consumer acceptance.The treatment provided consists of P0 (without fortificaton ofsour anchovy flour), P1 (fortifications of 40 grams of sour anchovy flour), P2 (fortifications of 60 grams of sour anchovy flour), P3 (fortifications of 80 grams of sour anchovy flour). Analysis parameters observed were sensory/consumer acceptance (appearance, odor, texture, and flavor) and proximate (moisture, protein, ash, fat, and carbohydrat contents). Based on this research, fortifications of 60 grams of sour anchovy flour (P2) produced the best sticks / preferred by 74 panelists (92.5%) with the appearance criteria was brownish yellow (3.27), the odor criteria was typical ofstickand odor of sour anchovy flour rather felt (3.50), the texture criteria was dry and crispy texture (3.07), the flavor was savory and sour anchovy flour was rather pronounced (3.32), with moisture, protein, ash, fat, and carbohydrate content was 5.33%, 10.62%, 3.83%, 28.57%, and 51.64%, respectively.Keywords: Stick,Flour, Stolephorus sp